2011
DOI: 10.1002/sim.4322
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup identification from randomized clinical trial data

Abstract: We consider the problem of identifying a subgroup of patients who may have an enhanced treatment effect in a randomized clinical trial, and it is desirable that the subgroup be defined by a limited number of covariates. For this problem, the development of a standard, pre-determined strategy may help to avoid the well-known dangers of subgroup analysis. We present a method developed to find subgroups of enhanced treatment effect. This method, referred to as "Virtual Twins", involves predicting response probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
629
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(632 citation statements)
references
References 22 publications
3
629
0
Order By: Relevance
“…The reason why we compare our sHinge method with the ROWSi is that Xu et al (2015) showed by simulation that the ROWSi was superior over the method solving (9) with h k replaced by the hinge loss, which was proposed in Zhao et al (2012) except that LASSO penalty instead of L 2 penalty was used for variable selection. Xu et al (2015) also showed by simulation that ROWSi was superior over other four recently proposed methods, the interaction tree by Su, Tsai, Wang, Nickerson, and Li (2009), the virtual twins by Foster, Taylor, and Ruberg (2011), the logistic regression with LASSO penalty by Qian and Murphy (2011), and the FindIt by Imai and Ratkovic (2013).…”
Section: Simulation Resultsmentioning
confidence: 88%
“…The reason why we compare our sHinge method with the ROWSi is that Xu et al (2015) showed by simulation that the ROWSi was superior over the method solving (9) with h k replaced by the hinge loss, which was proposed in Zhao et al (2012) except that LASSO penalty instead of L 2 penalty was used for variable selection. Xu et al (2015) also showed by simulation that ROWSi was superior over other four recently proposed methods, the interaction tree by Su, Tsai, Wang, Nickerson, and Li (2009), the virtual twins by Foster, Taylor, and Ruberg (2011), the logistic regression with LASSO penalty by Qian and Murphy (2011), and the FindIt by Imai and Ratkovic (2013).…”
Section: Simulation Resultsmentioning
confidence: 88%
“…There is a great variety of choices for in the literature on adaptive signature designs, 9,10 subgroup selection, [25][26][27] and optimal treatment regimes. [28][29][30][31][32][33] As a simple example, can be based on a working regression model such as…”
Section: A Two-stage Aedmentioning
confidence: 99%
“…Without appealing to a regression model, may be obtained from a specified parametric family 30,32,33 such as rectangles, or using nonparametric machine learning methods. 25,26,29,31 Except in Section 2.2.5, we do not assume that A = (Z 1 ) comes with an estimate of P(Y = 1|T, X).…”
Section: A Two-stage Aedmentioning
confidence: 99%
“…There is growing recognition of the importance of individual heterogeneity in treatment response, which has led to a rapid growth of methodological development in the area (1,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) …”
Section: Heterogeneity In Treatment Effects (Hte)mentioning
confidence: 99%